Analysis of the educational and professional programs of training of specialists in the specialty 231 social work - Kubitskyi, Serhii (ScienceRise: Pedagogical Education, 2017)
The results of analysis present educationally professional programs of training of future social workers in the institute of higher education in Ukraine in accordance with criteria: subject area; feature of the program; content and/or components of professional competence; predicted training results. The specific feature of the theoretical approaches to the training of specialists in the specialty 231 Social work is justified. The results of studying foreign experience of higher social education are presented It is well-proved that the sphere of professional training of future social workers needs specialization depending on the categories of clients of future professional activity. Expansion of fields of professional activity of the future social workers are directed on the increase of employment opportunities, however negatively represented on quality of professional training through supersaturating of content. It is proved that the most educational and professional programs require additions naturally scientific disciplines, which directly determine the future ability of graduating students for system thinking taking into account the state of environment. In comparing to the foreign programs of training of the social workers (USA, Great Britain, France), Ukrainian educational programs are not practice oriented; volume of educational time for practice is most often 10%, which is not sufficient for the formation of the competences